2021
DOI: 10.3389/fcimb.2021.665241
|View full text |Cite
|
Sign up to set email alerts
|

A New Optical Fiber Probe-Based Quantum Dots Immunofluorescence Biosensors in the Detection of Staphylococcus aureus

Abstract: Staphylococcus aureus (S. aureus) is one of the most common clinical pathogenic bacteria with strong pathogenicity and usually leads to various suppurative infections with high fatality. Traditional bacterial culture for the detection of S. aureus is prone to diagnosis and antimicrobial treatment delays because of its long-time consumption and low sensitivity. In this study, we successfully developed a quantum dots immunofluorescence biosensor for S. aureus detection. The biosensor combined the advantages of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 42 publications
(47 reference statements)
0
13
0
Order By: Relevance
“…In recent years, semiconductor QDs have witnessed a lot of attention due to their strong absorption, high stability and size-adjustable PL properties [71]. Different processes can be used to modify the surface of the QDs, allowing the experiment to obtain the QDs required [72].…”
Section: Inorganic-based Nanomaterialsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, semiconductor QDs have witnessed a lot of attention due to their strong absorption, high stability and size-adjustable PL properties [71]. Different processes can be used to modify the surface of the QDs, allowing the experiment to obtain the QDs required [72].…”
Section: Inorganic-based Nanomaterialsmentioning
confidence: 99%
“…Other than biomolecules, nanomaterials can also be used in the detection of cells and microorganism. In this context, Cui et al [72] developed the optical fiber probe and QDs immunofluorescence-based biosensor for detection of Staphylococcus aureus as shown in Figure 25. Developed biosensors exhibit advantage of high specificity between antigen and antibody's immune reaction, fluorescent labelling, transmission of fluorescent signal along optical fiber as well as high sensitivity and stability of QDs.…”
Section: Microorganism Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…These gratings achieve surface plasmon resonance (SPR) effects and selective or enzymatic coatings, respectively. For sensitive and precise detection of bacterial flora and biomolecules, optical biosensors based on fluorescence [ 35 , 36 , 37 , 38 , 39 ], SPR [ 3 , 5 , 13 , 40 , 41 ], and localized surface plasmon resonance (LSPR) [ 7 , 18 , 42 , 43 ] are currently being reported.…”
Section: Introductionmentioning
confidence: 99%
“…CdTe QDs have excellent fluorescence performance, and they have a wide and continuous excitation spectrum, a narrow and symmetrical emission spectrum, high quantum yield and strong fluorescence performance, which makes them suitable for fluorescence sensors and biological imaging [ 15 , 16 ]. Various studies have shown that QDs with functional modification can be used for immunofluorescence detection and labelling of living samples, especially in the field of drug analysis [ 17 ]. In this paper, QDs were used as a fluorescence probe to determine the content of FEL tablets in vitro.…”
Section: Introductionmentioning
confidence: 99%